TWO-DIMENSIONAL PH DISTRIBUTIONS AND DYNAMICS IN BIOTURBATED MARINE SEDIMENTS - Zhu Q.; Aller R.C.; Fan Y. (My University, 2006)
The seafloor is the site of intense biogeochemical and mineral dissolution-precipitation reactions which generate strong gradients in pH near the sediment-overlying water interface. These gradients are usually measured in one-dimension vertically with depth. Two-dimensional pH distributions in marine sediments were examined at high resolution (65 ? 65 ?m pixel) and analytical precision over areas of ?150 to 225 cm2 using a newly developed pH planar fluorosensor. Dramatic three-dimensional gradients, complex heterogeneity, and dynamic changes of pH occur in the surficial zone of deposits inhabited by macrofauna. pH can vary by ?2 units horizontally as well as vertically over millimeter scales. pH minima zones often form in association with redoxclines within a few millimeters of inner burrow walls, and become more pronounced with time if burrows remain stable and irrigated for extended periods. Microenvironmental pH minima also form locally around decaying biomass and relict burrow tracks, and dissipate with time (?5 d). H+ concentrations and fluxes in sandy mud show complex acid-base reaction distributions with net H+ fluxes around burrows up to ?12 nmol cm-2 d-1 and maximum net reaction rates varying between -90 (consumption) to 120 (production) ?M d-1 (?90 nmol cm-1 d-1 burrow length). Acid producing zones that surround irrigated burrows are largely balanced by acid titration zones along inner burrow walls and outer radial boundaries. The geometry and scaling of pH microenvironments are functions of diagenetic reaction rates and three-dimensional transport patterns determined by sediment properties, such as diffusive tortuosity, and by benthic community characteristics such as the abundance, mobility, and size of infauna. Previously, undocumented biogeochemical phenomena such as low pH regions associated with in-filled relict biogenic structures and burrowing tracks are readily demonstrated by two-dimensional and time-dependent images of pH and sedimentary structure.
Keywords: BIOGENIC STRUCTURE; BIOTURBATION; MARINE SEDIMENT; PH; REACTION RATE; SEAFLOOR